Differential effectiveness of COVID‐19 health behaviors: The role of mental health conditions in mask‐wearing, social distancing, and hygiene practice - Yusen Zhai; Xue Du (Wiley, 2023)
Abstract Background Mental health conditions are known to increase susceptibility to infectious diseases, including coronavirus disease 2019 (COVID‐19). Health behaviors play a crucial role in mitigating this susceptibility. We aim to examine the differential effectiveness of COVID‐19 preventive health behaviors among individuals, considering the presence or absence of specific mental health disorders. Methods Multivariable logistic regression with interaction terms was performed to examine whether associations between adherence to health behaviors and COVID‐19 infection were conditional on depression, anxiety, or eating disorders in a national sample of adults (N = 61,891) from 140 US universities, 2020-2021. Results Adjusting for age, race/ethnicity, and gender/sex, the effectiveness of mask‐wearing was significant and comparable among individuals with and without depression, anxiety, or eating disorders. Social distancing provided significantly less protection among individuals with depression, anxiety, or eating disorders. Hygiene practice provided significantly less protection among individuals with anxiety. Conclusion Mask‐wearing is robustly effective in the prevention of COVID‐19 among individuals. However, social distancing and hygiene practice provide less significant protection among individuals with certain mental health conditions, suggesting the importance of prioritizing these individuals for additional preventive measures (e.g., vaccines targeting variants) and mitigation strategies (e.g., financial assistance, targeted mental health care, health education).